Kohor retrospective study: development of children age 1-3 year with history of low born weigh (LBW) infants - Heni Puji Wahyuningsih; Indah Ajeng Pramesti; Endah Marianingsih Theresia (PUINOVAKESMAS, 2020)
Low Born Weigh (LBW) is a baby with a birth weight <2500 grams. LBW babies are weak in fine motor skills. If toddlers' developmental disorders are not detected early it will affect the quality of life, showed the prevalence of LBW by 5.52%. The prevalence of LBW infants in Bantul Regency from 2014 to 2018 has increased. The highest LBW cases were in the Pleret Puskesmas which reached 6.23%. The high prevalence of LBW in Pleret District has made researchers interested in researching the relationship of LBW history with the development of toddlers aged 1-3 years. The purpose of this research is to find out the influence of LBW history on the development of toddlers aged 1-3 years. This type of research is an observational analytic study with a retrospective cohort design. The sample in this study is toddlers aged 1-3 years in the district of Pleret. The independent variables of this study were the birth weight of infants and the dependent variable of development of infants aged 1-3 years. Statistical tests use the Chi-square test and relative risk. This research shows that as many as 31% of children under five with a history of LBW had inappropriate development status. The chi-square test showed a p-value of 0.016 (<0.05) which meant that there was a significant relationship between LBW history and the developmental status of toddlers. Obtained RR value of 1,250 (> 1,00), shows that toddlers with a history of LBW have a risk of experiencing developmental disorders 1.25 times greater than toddlers with normal weight history. The conclusion of this research is a there is a significant relationship between LBW history and the development of toddlers aged 1-3 years. Toddlers with an LBW history have a greater risk of developing developmental disorders compared to toddlers with normal weight history.